PEMIKIRAN AL-GAZALI DALAM EKONOMI ISLAM - Syaakir Sofyan (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2016)
Al-Gazali lives in agrarian life which is controlled by authorities who always oversees their workers. Meanwhile, those authorities try to find the legitimacy of their actions bureaucratically, or by appealing for religious leaders’ help in order to be leaved an instruction that supports their actions, or cultural onslaught where governments construct educational facilities. Al-Gazali’s thinkings about economy are based on tasawuf approach (approach of Sufism) due to his period of life, the wealthy, powerful, and prestigious are hard to take fiqih (jurisprudential) and philosophical approach in believing Yaum al-Hisab. In this regard, he focuses on individual behaviour that is being discussed based on perspective of al-Qur’an, Sunnah, sahabat and tabi’in’s instructions, and advices of Sufis who are prominent in his time.